Highly sensitive and wearable capacitive pressure sensors based on PVDF/BaTiO3 composite fibers on PDMS microcylindrical structures. (October 2022) - Yang, Chii-Rong; Lin, Ming-Feng; Huang, Chun-Kai; Huang, Wei-Chia; Tseng, Shih-Feng; Chiang, Hsin-Han
Graphical abstract: Highlights: Highly sensitive and wearable capacitive pressure sensors were developed. Microcylinder array and composite fibers were integrated as a dielectric layer. The sensor had a high sensitivity of 5 kPa −1 and fast response time of 25 ms. The proposed sensor with an extremely low detection limit of 0.11 Pa was verified. The sensor was applied as the E-skin for the touch switch of robotic arms. Abstract: This study developed a novel high-sensitivity flexible capacitive pressure sensor by combining BaTiO3 -doped polyvinylidene fluoride electrospinning fibers and polydimethylsiloxane microcylindrical structures as the dielectric layer. The flexible electrode formed by the graphene/PI film was assembled into a flexible capacitive pressure sensor, and formed a sandwich-like structure. The proposed sensor could obtain more capacitance variations and improve its sensitivity through composite deformation of electrospinning fiber and microcylindrical structure under pressure. The developed flexible capacitive pressure sensor has a high sensitivity of 5 kPa −1, fast response and release time of 25 and 50 ms, ultralow detection limit of 0.11 Pa, and more than 10000- and 5000-times compressions/bending cycling test without any signal attenuation for the high durability and high reliability. The results of this study proved that the sensors have excellent performance, and can be applied on wearable devices for human pulse monitoring and acoustic detection.